FACTORS CONTRIBUTING TO ONLINE DATING ROMANCE SCAM VICTIMIZATION: A QUALITATIVE STUDY - Annadorai, Kalaivani (International Journal of Psychosocial Rehabilitation, 2020)
Commercial crimes especially frauds and scams although not directly causing physical harms to human, they can ruin victims economically thus affecting their psychosocial well-being. Along this line of thought, online dating romance also known as Nigerian scam is where the scammer pretends to initiate a relationship with the aim to lure the potential victims of large sums of money. This mass marketing fraud will subsequently give negative impacts to the victims where the victims not only lose huge sums of money but also suffer psychological distress such as depression and stress. Although many researches have explored this area of study, studies in Malaysia is still limited. The aim of this study is to explore the vulnerability of the victims that led to this scam. Using a qualitative research design; victims, public prosecutors, the police, and non-government organization leaders were interviewed. Based on the data obtained from the informants, several themes were identified as contributory factors for this scam: loneliness, agreeableness, sensational seeking, lack of knowledge, and romantic belief. These factors can play a key role to authorities and the general public to curb this scam to some point and to educate and create self-awareness among the public.